WCM2016: MALACOLOGISTS OF THE WORLD TO CONVENE IN MALAYSIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 June 2015 World renowned scientists in the field of malacology (the study of snails and shellfish) will gather in Malaysia to discuss issues on conservation of molluscs (shellcovered organisms) that are increasingly threatened with extinction.